Diseño de una máquina para el corte de láminas de empaque flexible para flores en la empresa Cristapack S.A.S (2020)
This project aims to design a machine for cutting flexible packaging sheets for flowers in the company Inversiones Cristapack S.A.S. The increase in productivity and quality, impeding the reprocessing of the finished product and the physical involvement of operators by repetitive activities. For the fulfillment of the project carried out, an investigation of the affected cutting systems in the industry for flexible sheets was carried out, then the current parameters of the company, factors such as the product process, cutting methods used and variables involved were investigated . Next, the requirements of the company were defined both for production and those that solve the problem that the company has.